Social Psychology - Elliot Aronson; Wilson, Timothy D; Sommers, Samuel R; Page-Gould, Elizabeth; Lewis, Neil Jr (London Pearson, 2025)
social Psychology introduces the key concepts of the field through a storytelling approach that makes research relevant. Drawing upon their extensive experience as researchers and teachers, the authors present classic studies alongside the cutting-edge research that is the future of social psychology. The 11th Edition includes engaging contributions from new co-authors Elizabeth Page-Gould and Neil Lewis Jr. plus coverage of the COVID-19 pandemic, political upheaval in the US, and other recent developments through a social psychological lens.
Keywords: Social Psychology